ผลของโปรแกรมการจัดการตนเองร่วมกับการนวดกดจุดสะท้อนฝ่าเท้าต่ออาการปวดข้อเข่าในผู้ป่วยโรคข้อเข่าเสื่อมวัยผู้ใหญ่ - มารยาท เงินดี (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This quasi-experimental research aimed to study the effect of a self-management program combined with reflexology on joint pain among adult patients with knee osteoarthritis. Males and females with knee osteoarthritis, aged 40 - 59 years were recruited from the out-patient clinic, Siriraj hospital. The 44 samples purposively sampling; divided into control group and experimental group, 22 persons equally. Matched pair for gender, age, and body mass index. The control group was treated with conventional nursing care while the experimental group was treated with conventional nursing care plus an 8-week a self - management program combined with reflexology and pain score measurement both before and after the experiment. Research instruments were the self - management combined with reflexology program , and Numerical Rating Scale of pain. Descriptive statistics and t-test were used to analyze the data. The research findings were as follows: 1. The mean of the pain score in the group of patients with knee osteoarthritis receiving the self - management program combined with reflexology was significantly lower than that before receiving the program at the statistical level of .05. 2. After receiving the self - management program combined with reflexology, the mean of the pain score in experimental group was significantly lower than that in the control group at the statistical level of .05.